Effects of metomidate hydrochloride sedation on blood glucose and marketability of transported threespot gourami Trichogaster trichopterus - Crosby, Tina C (Journal of aquatic animal health, 2012)
Our objectives were to determine whether sedation with metomidate hydrochloride (hereafter, "metomidate") during transportation of threespot gourami Trichogaster trichopterus would prevent an increase in blood glucose levels and improve fish marketability (i.e., based on appearance and behavior) in comparison with unsedated controls. Threespot gourami are obligate air-breathers that possess a labyrinth organ, enabling the fish to respire air above the water surface; these fish should be lightly sedated during transport. Fish were transported for approximately 24 h via truck and domestic airline. Blood was sampled at 0, 2, 6, and 12 h posttransport ation, and appearance and behavior were observed at 0, 2, 4, 6, and 12 h and 7 d posttransportation. Metomidate concentrations tested were 0.0 (control), 0.1, 0.2, 0.3, and 0.4 mg/L. At the concentrations tested, metomidate neither inhibited elevations in blood glucose nor improved marketability. Fish that were transported with 0.3-mg/L metomidate were less marketable based on behavioral indices, and fish that were transported with 0.4-mg/L metomidate had higher glucose levels than control fish. Use of metomidate as a transport sedative for threespot gourami should be considered with caution and may be problematic at the concentrations tested; however, further research examining additional indices of stress may clarify metomidate use for this species